Sri Lanka: an island in turmoil - Anthony Goreau-Ponceaud; Delon Madavan (EchoGéo)
Sri Lanka is experiencing its worst economic crisis since its independence in 1948. Shortages and inflation of basic necessities (food, fuel, medicines) have provoked an unprecedented popular uprising of Sri Lankans since March 2022, across ethnic and religious divides, which led to the flight of President Gotabaya Rajapaksa on July 9, 2022, and his resignation a few days later, putting an end to almost two decades of rule by the Rajapaksa brothers. This article looks back at the causes of this political, economic, social and now humanitarian crisis to glimpse the unprecedented nature of this protest and to question the mobilization of civil societies in an island long marked by the polarization of political life, and finally the geopolitical effects of this multifaceted crisis.